Patterns of Substance Use among HIV-Positive Adults Over 50: Implications for Treatment and Medication Adherence - Parsons, Jeffrey T. (2014)
BACKGROUND: The population of older adults living with HIV is increasing in the United States. Despite an increased focus on the health of HIV-positive older adults, knowledge about their substance use, a primary risk factor for HIV medication non-adherence, and the association between use, problems associated with use, and adherence behavior, is limited. METHODS: Data were collected from 557 HIV-positive adults aged 50 and older in the New York City area via telephone interview. Participants reported the number of days in the past month on which they missed any doses of HIV medication as well as the number of days they used alcohol, marijuana, cocaine/crack, opiates, amyl nitrite (poppers), and other drugs. The severity of substance use associated problems was assessed using the DAST-10 and AUDIT-C. RESULTS: The sample included gay/bisexual (40.4%) and heterosexual (28.1%) men as well as lesbian/bisexual (4.9%) and heterosexual (26.7%) women. Latent class analyses identified four distinct patterns of substance use: Exclusive Alcohol Use; Alcohol and Marijuana; Alcohol and Cocaine/Crack; and Multiple-Substance Use. Variability in the number of missed HIV medication days and perceptions of substance use associated problems were observed across classes, with poorest adherence reported in the Alcohol and Cocaine/Crack class, followed by the Multiple-Substance Use class. These two classes also reported the greatest perceived impairment from substance use. CONCLUSIONS: Patterns of recent substance use were associated with varying levels of HIV medication adherence and perceived substance use impairment, indicating that substance type matters when considering the health of older adults living with HIV, and that multiple-substance use needs to be addressed by interventions aimed at improving medication adherence.